SPINK2 deficiency causes infertility by inducing sperm defects in heterozygotes and azoospermia in homozygotes. Issue 8 (29th May 2017) - Kherraf, Zine‐Eddine; Christou‐Kent, Marie; Karaouzene, Thomas; Amiri‐Yekta, Amir; Martinez, Guillaume; Vargas, Alexandra S; Lambert, Emeline; Borel, Christelle; Dorphin, Béatrice; Aknin‐Seifer, Isabelle; Mitchell, Michael J; Metzler‐Guillemain, Catherine; et al.
Abstract: Azoospermia, characterized by the absence of spermatozoa in the ejaculate, is a common cause of male infertility with a poorly characterized etiology. Exome sequencing analysis of two azoospermic brothers allowed the identification of a homozygous splice mutation in SPINK2, encoding a serine protease inhibitor believed to target acrosin, the main sperm acrosomal protease. In accord with these findings, we observed that homozygous Spink2 KO male mice had azoospermia. Moreover, despite normal fertility, heterozygous male mice had a high rate of morphologically abnormal spermatozoa and a reduced sperm motility. Further analysis demonstrated that in the absence of Spink2, protease‐induced stress initiates Golgi fragmentation and prevents acrosome biogenesis leading to spermatid differentiation arrest. We also observed a deleterious effect of acrosin overexpression in HEK cells, effect that was alleviated by SPINK2 coexpression confirming its role as acrosin inhibitor. These results demonstrate that SPINK2 is necessary to neutralize proteases during their cellular transit toward the acrosome and that its deficiency induces a pathological continuum ranging from oligoasthenoteratozoospermia in heterozygotes to azoospermia in homozygotes. Synopsis: SPINK2, a serine protease inhibitor, is believed to target the acrosin, the main sperm acrosomal protease. This study confirms SPINK2 in that role and finds it essential for spermiogenesis as SPINK2 deficiency induces a post meiotic block at the round spermatid stage leading to azoospermia in mice and men. In round spermatids, SPINK2 is necessary to inactivate the acrosin during its transit through the endoplasmic reticulum and the Golgi apparatus. In the absence of SPINK2, acrosin can auto‐activate, disorganize the Golgi apparatus, prevent the production of the acrosome and induce a block at the round spermatid stage. A reduced amount of SPINK2 in heterozygotes is also deleterious, inducing a milder phenotype of oligozoospermia and/or teratozoospermia without a systematic infertility. Abstract : SPINK2, a serine protease inhibitor, is believed to target the acrosin, the main sperm acrosomal protease. This study confirms SPINK2 in that role and finds it essential for spermiogenesis as SPINK2 deficiency induces a post meiotic block at the round spermatid stage leading to azoospermia in mice and men.